2010
DOI: 10.1111/j.1365-2125.2010.03648.x
|View full text |Cite
|
Sign up to set email alerts
|

Rupatadine does not potentiate the CNS depressant effects of lorazepam: randomized, double‐blind, crossover, repeated dose, placebo‐controlled study

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Although one defining characteristic of second generation H1-antihistamines is their lack of CNS effects, it has been proved that some compounds of this group are not devoid of such effects.• There is evidence that second generation H1-antihistamine compounds without relevant CNS effects at therapeutic doses could increase the behavioural impairment produced by sedating drugs when both are taken concomitantly.• The evaluation of possible drug interactions is crucial, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Novel agents, such as rupatadine, an H 1 -antihistamine/anti-platelet-activating factor agent, 23,24,66,71,123,125 might play a unique role. H 3 -antihistamines lead to an increase in norepinephrine and might have an advantageous decongestant effect in patients with allergic rhinitis administered with or without H 1 -antihistamines.…”
Section: Future Directionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Novel agents, such as rupatadine, an H 1 -antihistamine/anti-platelet-activating factor agent, 23,24,66,71,123,125 might play a unique role. H 3 -antihistamines lead to an increase in norepinephrine and might have an advantageous decongestant effect in patients with allergic rhinitis administered with or without H 1 -antihistamines.…”
Section: Future Directionsmentioning
confidence: 98%
“…Second-generation H 1 -antihistamines do not exacerbate the CNS effects of concurrently used ethanol, benzodiazepines, and other CNS-active substances. 1,18,31,33,[96][97][98]123 About 15 years ago, regulatory agencies rescinded their approval for astemizole and terfenadine, the second-generation H 1 -antihistamines initially introduced, because they potentially cause QT interval prolongation and torsade de pointes. Subsequently, regulatory agencies have scrutinized all secondgeneration H 1 -antihistamines for their proarrhythmic potential and required studies of their cardiac safety at standard doses and high off-label doses, as well as drug interaction studies and studies in the elderly and other vulnerable patients.…”
Section: Second (New)-generation H 1 -Antihistaminesmentioning
confidence: 99%
“…No interaction was observed when rupatadine was coadministered with fluoxetine (a substrate of CYP2D6) or ethanol . In studies performed in healthy volunteers, no clinically meaningful interaction was observed when rupatadine was coadministered with azithromycin [a gastrointestinal P‐glycoprotein (Pgp) substrate] and rupatadine did not potentiate the CNS depressant effects of lorazepam . Nevertheless, as with other antihistamines, interactions with CNS depressants cannot be excluded.…”
Section: Clinical Pharmacology Of Rupatadinementioning
confidence: 99%
“…We selected the battery of tests based on our previous experience performing similar studies (Barbanoj et al ., , ; García‐Gea et al ., , ). In addition, these tests enable us to evaluate psychomotor performance in standardized conditions with little interference from other factors, such as interindividual or cultural differences.…”
Section: Methodsmentioning
confidence: 99%